AN EPIDEMICAL STUDY ON THE TOXOPLASMA PARASITE IN IRAQ - Sura Samer Alwan (Web of Journals Publishing, 2025)
One of the prevention ways is to prevent the contamination of at-risk groups, especially women of reproductive age (14-45 years old) with health education. One of the specific goals of this research is to identify seronegative girls in Iraq so that by using it, we can plan the necessary training and actions to prevent this parasite. 1000 blood samples were collected randomly from high school students all over Iraq for 10 months and tested by indirect immunofluorescence method. Also, a questionnaire was organized and available to the public, and information such as history of contact with cats, history of eating semi-cooked meats, eating raw liver was collected. The χ2 statistical method was used to correlate the epidemiological findings of the infection and the antibody titer, and the results were analyzed using SPSS software. A significance level of 0.05 was considered. The level of IgG antibody against Toxoplasma was positive in 8.21% of the studied subjects by indirect immunofluorescence method. In 198 people (8.91%), the antibody titer by indirect immunofluorescence method was 1:20 to 1:100, and in 20 people (2%) the antibody titer was more than 1:100. The highest percentage of infection was determined in people who kept cats at home (5.37%) and students who had general symptoms (fever, lymphadenopathy, and skin rashes) (7.37%). The χ2 statistical test showed that there is a significant relationship between infection and contact with cats, eating raw liver, and disease symptoms. Based on the results, it is observed that the antibody titer was negative in 2.78% of the people of the considered society; That is, these people lack any acquired immunity against this infection. Therefore, there is a possibility that the children of these people will become toxoplasma.
Keywords: Epidemiology, Toxicology, Toxoplasma, parasite, Iraq.